2016
DOI: 10.1002/pssa.201600489
|View full text |Cite
|
Sign up to set email alerts
|

Vertical GaN bipolar devices: Gaining competitive advantage from photon recycling

Abstract: It is shown that peripheral current Ip flows in non‐self‐aligned mesa‐type p–n diodes but that Ip flowing in GaN diodes cannot be explained by elongated minority‐carrier lifetime associated with intrinsic photon recycling (IPR), i.e., reabsorption of radiative recombination. Accordingly, possible increase in the ratio of deep Mg acceptors (energy level: EA) due to extrinsic photon recycling (EPR) is proposed, and the effect of EPR is expressed as an effective EA. Due to the limit on the power dissipation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…On M-3D (0001) substrates, Ohta et al fabricated GaN p + n diodes, whose epitaxial layers consisted of a 30 nm p ++ GaN (magnesium concentration [Mg] = 2 × 10 20 cm −3 ) cap layer for anode ohmic contacts, a 500 nm p + GaN ([Mg] = 1 × 10 18 cm −3 ) layer, a 13 μm n-GaN (net donor density N D −N A = 7 × 10 15 cm −3 ) drift layer, and a 2 μm n + GaN (silicon concentration [Si] = 2 × 10 18 cm −3 ) buffer layer. 16) They observed a rapid increase in the forward current I F of a 100 μm diameter GaN p + n diode at a forward voltage (V F ) exceeding 5.5 V. 16) They attributed such I F increase to photon recycling, 13,14,[17][18][19][20][21][22][23] which can be categorized as "intrinsic photon recycling" (IPR) by band-toband transitions and "extrinsic photon recycling" (EPR) by transitions involving forbidden-gap energy levels. 17) IPR increases minority-carrier lifetime, 24) whereas EPR involving deep acceptors or deep donors increases the ionization ratio (r) of those dopants.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…On M-3D (0001) substrates, Ohta et al fabricated GaN p + n diodes, whose epitaxial layers consisted of a 30 nm p ++ GaN (magnesium concentration [Mg] = 2 × 10 20 cm −3 ) cap layer for anode ohmic contacts, a 500 nm p + GaN ([Mg] = 1 × 10 18 cm −3 ) layer, a 13 μm n-GaN (net donor density N D −N A = 7 × 10 15 cm −3 ) drift layer, and a 2 μm n + GaN (silicon concentration [Si] = 2 × 10 18 cm −3 ) buffer layer. 16) They observed a rapid increase in the forward current I F of a 100 μm diameter GaN p + n diode at a forward voltage (V F ) exceeding 5.5 V. 16) They attributed such I F increase to photon recycling, 13,14,[17][18][19][20][21][22][23] which can be categorized as "intrinsic photon recycling" (IPR) by band-toband transitions and "extrinsic photon recycling" (EPR) by transitions involving forbidden-gap energy levels. 17) IPR increases minority-carrier lifetime, 24) whereas EPR involving deep acceptors or deep donors increases the ionization ratio (r) of those dopants.…”
mentioning
confidence: 99%
“…In the case of magnesium-doped GaN at room temperature, Ishida et al observed electroluminescence peaking at 3.38 eV, 25) which results in photoexcitation of an electron from an ionized magnesium acceptor to the conduction-band. The resultant neutralized acceptor is ionized through electron capture from the valence-band, leading to the increased r. 13,[17][18][19][20][21][22]25) The conductivity of an n-type drift layer can also be enhanced by hole traps. Here the "hole trap" means that the charge state of the trap is determined primarily by the hole concentration p. Manifacier et al carried out one-dimensional simulation of I F /V F characteristics of a GaAs p + n diode consisting of a 0.1 μm p + GaAs (p = 1 × 10 18 cm −3 ) layer, a 10 μm n-GaAs (N D −N A = 1 × 10 16 cm −3 ; electron mobility μ n = 4000 cm 2 V −1 s −1 ; hole mobility μ p = 280 cm 2 V −1 s −1 ; electron lifetime τ n = 10 ns; hole lifetime τ p = 10 ns) drift layer, and a 0.1 μm n + GaAs (electron concentration n = 1 × 10 18 cm −3 ) layer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of third-generation wide-bandgap semiconductor materials has received more attention due to the increase in demand for high-power, high-temperature, and high-frequency electronic devices used in the aerospace industry, electric vehicles, and advanced nuclear systems. Especially, silicon carbide (SiC) based highly efficient power electronic devices have fascinated more in achieving an advanced energy-saving society because of its superior material properties such as high thermal conductivity, mechanical stability, and so forth. However, the lack of a large area on the SiC substrate limits the production of large scale SiC-based devices. To solve this problem, the epitaxial growth of SiC film on the Si substrate has been proposed in recent decades, as it could be easily done by chemical vapor deposition (CVD). However, the significant lattice and thermal expansion coefficient mismatches between Si and SiC leads to a higher concentration of crystalline defects inside the layers, which affects the breakdown voltage and carrier mobility. ,, …”
mentioning
confidence: 99%